Functional Analysis of KIF3A and KIF3B during Spermiogenesis of Chinese Mitten Crab Eriocheir sinensis. - Yang Lu (Public Library of Science (PLoS), 2014)
Background Spermatogenesis represents the transformation process at the level of cellular development. KIF3A and KIF3B are believed to play some roles in the assembly and maintenance of flagella, intracellular transport of materials including organelles and proteins, and other unknown functions during this process. During spermatogenesis in Eriocheir sinensis, if the sperm shaping machinery is dependent on KIF3A and KIF3B remains unknown. Methodology/principal findings The cDNA of KIF3A and KIF3B were obtained by designing degenerate primers, 3'RACE, and 5'RACE. We detected the genetic presence of kif3a and kif3b in the heart, muscle, liver, gill, and testis of E. sinensis through RT-PCR. By western blot analysis, the protein presence of KIF3A and KIF3B in heart, muscle, gill, and testis reflected the content in protein level. Using in situ hybridization and immunofluorescence, we could track the dynamic location of KIF3A and KIF3B during different developmental phases of sperm. KIF3A and KIF3B were found surrounding the nucleus in early spermatids. In intermediate spermatids, these proteins expressed at high levels around the nucleus and extended to the final phase. During the nuclear shaping period, KIF3A and KIF3B reached their maximum in the late spermatids and were located around the nucleus and concentrated in the acrosome to some extent. Conclusions/significance Our results revealed that KIF3A and KIF3B were involved in the nuclear and cellular morphogenesis at the levels of mRNA and protein. These proteins can potentially facilitate the intracellular transport of organelles, proteins, and other cargoes. The results represent the functions of KIF3A and KIF3B in the spermatogenesis of Crustacea and clarify phylogenetic relationships among the Decapoda.